Additional file 1 of Location of studies and evidence of effects of herbivory on Arctic vegetation: a systematic map - E. M. Soininen (11566553); I. C. Barrio (11566556); R. Bjørkås (11566559); K. Björnsdóttir (11566562); D. Ehrich (11566565); K. A. Hopping (11566568); E. Kaarlejärvi (11566571); A. L. Kolstad (11566574); S. Abdulmanova (11566577); R. G. Björk (11566580); C. G. Bueno (11566583); I. Eischeid (11566586); et al. (2021)
Additional file 1. Additional information on literature searches. ROSES form systematic map.